Milk market of small scale artisan cheese factories in selected livestock watersheds of Honduras and Nicaragua - Holmann, Federico J. (2001)
Surveys were made of rural artisan cheese factories located in the region of Olancho, Catacamas, and Juticalpa in Honduras (n=10) and in Esquipulas and Muy-Muy in Nicaragua (n=13). The objective was to analyze the milk market of small rural artisan cheese factories in livestock watersheds of Honduras and Nicaragua to determine if there is a market for higher milk production; how much additional milk can the market absorb in each season of the year; there is a market for milk of higher hygienic quality. The main buyer of the milk from small and medium scale farmers in Honduras and Nicaragua is the rural artisan cheese industry, which absorbs almost 80% of the milk produced in both countries. Total milk production during the rainy season is about twice that during the dry season, causing an over-supply and scarcity of milk, respectively. The shortage of fluid milk during the dry season leads to an unsatisfied market. The artisan cheese factories in Honduras and Nicaragua would be willing to buy 76% and 55% more milk during the dry season, but this supply is not available due low milk productivity. This fact suggests that an aggressive program for the promotion of shrub legumes with sugarcane to supplement the herd during the dry season would have more impact that the promotion of grasses or legumes for the rainy season when there is little market for additional milk produced. In addition, rural artisan cheese factories in Honduras and Nicaragua, that consider the milk they collect is of bad quality, would be willing to pay a higher price if the option to collect milk of better hygienic quality exists. In Honduras this price would be about 9 % higher during the dry season and 11% higher during the rainy season. In Nicaragua the cheese factories would be willing to pay a milk price which is 17% higher, but only during the rainy season. As a result, large incentives exist in both countries to increase milk production during the dry season and to improve the hygienic quality of milk in the studied areas.